2003
DOI: 10.1177/1534735403256207
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Survey of Complementary and Alternative Medicine Use in Men Recently Diagnosed with Prostate Cancer

Abstract: More than one third of recently diagnosed prostate cancer patients utilize some form of CAM therapy, and the majority disclose their use to their physician(s). However, they tend to rely on anecdotal information for their CAM decision making. Dissemination of reliable CAM information is one key to helping men navigate this difficult arena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 15 publications
(23 reference statements)
3
63
2
2
Order By: Relevance
“…However, only 17 of these studies focused exclusively on men with prostate cancer. 22,24,28,29,34,36,37,39,40,50,51,54,56,[58][59][60]62 The remaining studies collected data from broader study populations and reported the prevalence of CAM use for subgroups including men with prostate cancer. 23,[25][26][27][30][31][32][33]35,38,[41][42][43][44][45][46][47][48][49]52,53,55,57,61,63 The characteristics of all 42 included studies are summarised in Table 2 …”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, only 17 of these studies focused exclusively on men with prostate cancer. 22,24,28,29,34,36,37,39,40,50,51,54,56,[58][59][60]62 The remaining studies collected data from broader study populations and reported the prevalence of CAM use for subgroups including men with prostate cancer. 23,[25][26][27][30][31][32][33]35,38,[41][42][43][44][45][46][47][48][49]52,53,55,57,61,63 The characteristics of all 42 included studies are summarised in Table 2 …”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29]31,33,34, Across these studies, the prevalence of CAM use ranged from 8 to 90%, while the interquartile range was 25-43% (median ¼ 30%). Sollner et al 55 report the lowest prevalence rate (8%), but this is based on a very small sample size (n ¼ 12).…”
Section: Prevalence Of Cam Usementioning
confidence: 99%
See 3 more Smart Citations